Brown adipose tissue is associated with cardiometabolic health - Becher, Tobias; Palanisamy, Srikanth; Kramer, Daniel J.; Eljalby, Mahmoud; Marx, Sarah J.; Wibmer, Andreas G.; Butler, Scott D.; Jiang, Caroline S.; Vaughan, Roger; Schöder, Heiko; Mark, Allyn; Cohen, Paul (Nature medicine, 2021)
White fat stores excess energy, whereas brown and beige fat are thermogenic and dissipate energy as heat. Thermogenic adipose tissues markedly improve glucose and lipid homeostasis in mouse models, although the extent to which brown adipose tissue (BAT) influences metabolic and cardiovascular disease in humans is unclear1,2. Here we retrospectively categorized 134,529 18F-fluorodeoxyglucose positron emission tomography-computed tomography scans from 52,487 patients, by presence or absence of BAT, and used propensity score matching to assemble a study cohort. Scans in the study population were initially conducted for indications related to cancer diagnosis, treatment or surveillance, without previous stimulation. We report that individuals with BAT had lower prevalences of cardiometabolic diseases, and the presence of BAT was independently correlated with lower odds of type 2 diabetes, dyslipidemia, coronary artery disease, cerebrovascular disease, congestive heart failure and hypertension. These findings were supported by improved blood glucose, triglyceride and high-density lipoprotein values. The beneficial effects of BAT were more pronounced in individuals with overweight or obesity, indicating that BAT might play a role in mitigating the deleterious effects of obesity. Taken together, our findings highlight a potential role for BAT in promoting cardiometabolic health.